2021
DOI: 10.1002/chem.202004516
|View full text |Cite
|
Sign up to set email alerts
|

Selective Formation of Polyaniline Confined in the Nanopores of a Metal–Organic Framework for Supercapacitors

Abstract: In this study, a strategy that can result in the polyaniline (PANI) solely confined within the nanopores of a metal–organic framework (MOF) without forming obvious bulk PANI between MOF crystals is developed. A water‐stable zirconium‐based MOF, UiO‐66‐NH2, is selected as the MOF material. The polymerization of aniline is initiated in the acidic suspension of UiO‐66‐NH2 nanocrystals in the presence of excess poly(sodium 4‐styrenesulfonate) (PSS). Since the pore size of UiO‐66‐NH2 is too small to enable the inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 70 publications
2
55
0
Order By: Relevance
“…As shown in Figure S14, its area capacitance remains 71% of its initial value after 2000 cycles of the charge–discharge processes. Table S2 shows a partial list of MOF-based materials that have been reported for supercapacitors along with their capacitive performances. ,, Compared to most reported MOF-based materials, Ce-MOF-808–20CNT exhibits a higher or comparable area capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S14, its area capacitance remains 71% of its initial value after 2000 cycles of the charge–discharge processes. Table S2 shows a partial list of MOF-based materials that have been reported for supercapacitors along with their capacitive performances. ,, Compared to most reported MOF-based materials, Ce-MOF-808–20CNT exhibits a higher or comparable area capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is then crucial to ensure that the crystallinity of the tested MOF can be preserved after pressing it into the pellet. Pressures of 50–200 MPa were commonly used to prepare the MOF pellets, ,, and in our previous studies, a pressure of 115 MPa was used for preparing pellets of other Zr-MOFs. , Thus, pellets of Zr-MOF-808, Ce-MOF-808, and bimetallic MOF-808 were first prepared with a load of 0.5 ton, i.e ., a pressure of 115 MPa. XRD patterns of the resulting pellets were thereafter collected.…”
Section: Resultsmentioning
confidence: 99%
“…The pellets of Zr-MOF-808, Ce-MOF-808, and bimetallic MOF-808 were prepared by the following procedure to measure their electrical conductivities and proton conductivities; a similar protocol has been used to prepare both Zr-MOF pellets and Ce-MOF pellets in our previous studies. Approximately 15 mg of MOF powder was packed into a 7 mm die set and pressed into a pellet by a minipellet press (Specac). The load of the minipellet press used here was set as 0.1 ton; this pressure is lower than that used in our previous studies, as discussed in the text regarding Figure later.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also demonstrated the efficient confinement of PANI chains within the pores of UiO-66-NH 2 , with a positive impact on the stability of the PANI chains observed upon extended cycling. 32 Attempts were also successfully made to link the observed enhancement to the intrinsic microporosity of the MOFs and the electrical conductivity of the PANI. 33 However, a deeper understanding of the underlying mechanism for this observed synergy is still lacking.…”
Section: Introductionmentioning
confidence: 99%